Identity and Humor in Never Have I Ever - Dolai , Ankita (AMERICANA E-journal of American Studies in Hungary, 2023)
Reading the TV series Never Have I Ever (2020-2023) through the lens of dramedy highlights not only the experiences of its tragicomic protagonist, the 15-year-old Indian American protagonist Devi Vishwakumar, but also the humorous portrayal of her ambivalent relationship to her mother Nalini in the context of Indian American diaspora formations. Devi is portrayed as extremely intelligent, yet also as insecure, rebellious and awkward, reflecting a multi-faceted and flawed brown teenage character beyond the common caricature of an Indian immigrant background. The show reveals that her inclination towards Western and American lifestyle does not so much emerge because she rejects her cultural background, but because she is confused about how to navigate her multi-layered identity and carve out her own sense of self. Humor in the show exposes the silliness of perceived stereotypes associated with Indian culture, while at the same time questioning and resisting them through its complex characters. Although, her mother, Nalini represents the conservative and restrictive Indian part of Devi’s identity and forces her to embrace it, Nalini also follows her own desires and rejects certain prescribed norms that come with her role as an Indian mother. This paper analyses how the show’s complex characters and mother-daughter relationship subverts generational stereotypes surrounding diasporic identities and Indian motherhood through the genre elements of dramedy and high school melodrama.